Acurácia do peso fetal estimado na ultrassonografia em relação ao peso dos recém-nascidos quando menor que 2500g e a partir de 4000g no serviço de medicina fetal do HUSM - Araujo, Gabriel Karam de (2023)
The previous diagnosis of small (SGA) and large for gestational age (LGA) fetuses can lead to measures that reduce adverse neonatal outcomes, since both are known to have higher rates of perinatal mortality and morbidity. SGA fetuses are at increased risk for prematurity, perinatal hypoxia, hypothermia, and hypoglycemia; or else, in LGA fetuses, there is an increased chance of shoulder dystocia, brachial plexus and facial nerve injury, postpartum hemorrhage, and trauma to the birth canal at birth. The diagnosis is preferably performed by ultrasound examination with fetal biometry in the third trimester and maternalfetal factors may contribute to this prediction of estimated fetal weight change. To propose preventive measures, a diagnosis prior to birth is necessary. Objectives: To evaluate the fetal weight at birth and correlate it with the estimated fetal weight in the last ultrasound, considering that the decision of the best moment for the birth of SGA and LGA fetuses is of great value in changing the neonatal outcome. Methods: The study complied with ethical, being approved by the UFSM Ethics Committee. This is a retrospective observational study carried out at the HUSM Fetal Medicine outpatient clinic. The fetal weight estimated in ultrasound was recorded in pregnant patients (n = 99) at the Hospital Universitário de Santa Maria (HUSM) in the third trimester, who underwent the examination at the fetal medicine service within fifteen days before delivery at the institution, with fetal weight estimated in an ultrasound examination less than 2500g and greater than or equal to 4000g and correlated with data on fetal weight at birth, determined by a specific scale for newborns. Study data were obtained from birth records in the medical records. Descriptive analysis was used to compare the distribution of independent variables, focusing on frequency, and results expressed as mean, standard deviation, minimum value presented and maximum value presented, as well as relative and absolute frequencies. The normality of data distribution was tested using the Kolmogorov-Smirnov test. Pearson's correlation coefficient was used to verify the crude relationship between PEF and PN. A significance level of 5% was considered satisfactory. Results: There was a high linear correlation between estimated fetal weight and birth weight (R=0.92) and the difference between them varied between -488 g and +609 g, with a mean of +60g. Most of the maximum percentage variations of the weight estimate were around 10%. The PEF had a sensitivity of 89.7% and a specificity of 100%, with an agreement percentage of 90% of the cases. Conclusions: the PEF is capable of adequately predicting the BW of SGA and LGA fetuses in the Fetal Medicine service of the HUSM, showing high accuracy, regardless of the training phase in which the resident physician of this service is.